PCS-3 Toxicity Sub-cronic Ethanolic Extract of Malaka (Phyllanthus emblica) Leaves on Kidney Function of Mice (Mus musculus) be Reviewed from Blood Creatinin Level - N Asmilia; D Aliza; T Armansyah TR; Rusli Rusli; N Tridayanti (Hemera Zoa, 2018)
Herbal medicine is still the mainstay of about 75-80% of the whole population, and the major part of traditional therapy involves the use of plant extract and their active constituents in the indigenous. The plant genus Phyllantus is widely distributed in most of tropical and subtropical countries like China, India, Southeast Asia and Indonesia [1,2]. Phyllantus spesies have long been used in folk medicine to tread a broad spectrum of disorders. Phyllantus emblica or Indian gooseberry (Figure 1), belonging to family Euphorbeaceae has been reported to have antioxidant, anti-inflammatory, anticancer, adaptogenic, anti-diabetic, antimicrobial and immunomodulatory potential [3]. The aim of the study was to investigate the effect of ethanolic extract of malaka leaves (Phyllanthus emblica) on renal function by analyzing creatinine level in mice blood (Mus musculus).